2014
DOI: 10.1364/boe.5.003103
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of MRI-guided near-infrared spectroscopy clinical breast exam data and its impact on diagnostic performance

Abstract: Abstract:In this study, data from breast MRI-guided near infrared spectroscopy (NIRS) exams delivered to 44 patients scheduled for surgical resection (ending in 16 benign and 28 malignant diagnoses) were analyzed using a spatial sensitivity metric to quantify the adequacy of the optical measurements for interrogating the tumor region of interest, as derived from the concurrent MRI scan. Along with positional sensitivity, the incorporation of spectral priors and the selection of an appropriate regularization pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Some MRI/NIRST examinations (14 in total) were excluded from the analysis based on a quantitative and objective assessment of the optical signal sampling of the MRI contrast-enhancing ROIs, which we attribute to the incomplete breast coverage that occurs with the current version of the optical imaging breast interface used in this study (10). The optical signal cutoff used to define an evaluable MRI/NIRST examination was based on its measurement sensitivity to the contrast-enhancing ROI because the optical measurements did not adequately interrogate the ROI in every case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some MRI/NIRST examinations (14 in total) were excluded from the analysis based on a quantitative and objective assessment of the optical signal sampling of the MRI contrast-enhancing ROIs, which we attribute to the incomplete breast coverage that occurs with the current version of the optical imaging breast interface used in this study (10). The optical signal cutoff used to define an evaluable MRI/NIRST examination was based on its measurement sensitivity to the contrast-enhancing ROI because the optical measurements did not adequately interrogate the ROI in every case.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen examinations were excluded from analysis because of insufficient coverage of the region of suspicion by the optical fiber array. Previous work (16, 18) has shown that optical image accuracy depends on having light signals that propagate through the abnormal region of interest with sufficient strength to be detected above the noise floor of the optical imaging array, and a measurement signal cutoff of 0.75% lesion sensitivity (relative to total sensitivity) was considered (10) as the minimum acceptable data sensitivity to the tissue region under evaluation. Based upon this analysis, data from 30 patient examinations met the signal sensitivity cutoff criterion, indicating that the breasts of these patients were accurately imaged across the plane of the tumor, and were subsequently evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information about the instrumentation can be found in previous publications [1,4,5]. The device included six FD wavelengths (spanning from 660nm to 850nm) and three CW wavelengths (900nm to 950nm).…”
Section: Imaging Proceduresmentioning
confidence: 99%
“…Near-Infrared Spectral Tomography (NIRST) has shown a good potential for breast cancer characterization [1][2][3][4][5]. The image reconstruction of NIRST is a typically ill-posed, ill-conditioned and nonlinear inverse problem because of the high degree of light scattering and a limited number of boundary measurements [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%